“构式-语块”理论与国际 汉 语教学研究的新视角——以现 代汉语补语为例 = “Construction-Chunk” Theory and the New Angle of International Chinese Teaching and Research: A Case Analysis on Complements of Mandarin Chinese - Fang, Zhou (Sinología hispánica. China Studies Review, 2015)
在对外汉语教学和国际汉语教学50 多年 的发展历程中，由于受到现代汉语传统语法研 究的影响，语法教学（即句法规则的教学）与 词汇教学一直相互脱节，真实语言中大量介于 词和句子之间的语言单位受到忽略，而这些语 言单位在对外汉语词汇教学和语法教学中都起 着重要的作用，是各类教学法都不可忽视的一 个环节。本文尝试以“构式-语块”理论为依据， 从搭配的视角对现代汉语中的补语进行分析和 阐释，以此探讨“构式-语块”理论对国际汉语 教学和研究的意义 In the past fifty years, under the influence of traditional grammatical study of modern Chinese, people working in the field of teaching Chinese as a second language and International Chinese Teaching have been treating grammar teaching (i.e. teaching of sentence patterns) and vocabulary teaching as two independent parts. As a result, many language units between lexical words and sentences in real life communication have been neglected although these units play an important role in both vocabulary teaching and sentence pattern teaching in International Chinese Teaching and deserve due attention within any teaching approach. Based on the “Construction-Chunk” Theory, and guided by the concept of “collocation”, the article analyses complements of Mandarin Chinese in order to discuss the function of the “Construction-Chunk” Theory on International Chinese Teaching and research